Comparing AHP and ELECTRE I for prioritizing software requirements - Fernandes, Joao M.; Prozil Rodrigues, Susana; Costa, Lino A. (2015 IEEE/ACIS 16th International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD), 2015)
Requirement prioritization is a process that allows selection of the "key" candidate requirements, the ones that are the most important for the construction of quality and cost-controlled software. Requirement prioritization brings certain issues and challenges related with the different stakeholders involved in the project, as well as with the prioritization techniques used, which differ in procedures, criteria and metrics. This manuscript compares two multi-criteria decision methods (MCDM), AHP and ELECTRE I, seeking to justify which one is the most feasible in the requirement prioritization process of a real-world case study. To accomplish this aim, several criteria were used to compare the applicability and performance of both MCDMs. In order to reflect reality as close as possible, several stakeholders, including software professionals directly related to the case study, were involved. The results confirm the intuition that ELECTRE I is more easily applicable than AHP. ELECTRE I is subject to fewer mistakes in comparisons of the requirements than the AHP method, as these are carried out differently. In fact, due to its inherent complexity, AHP becomes even impractical in software projects with a large number of requirements.